A Case of Metastatic Prostate Cancer to the Distal Phalanx. (May 2022) - Lander, Richard D.; O'Donnell, Marc J.
Metastatic bone tumors to the hand are extremely rare. We present a case of metastatic prostate cancer to the right middle finger distal phalanx. To our knowledge, there is one other case of metastatic prostate cancer to the hand in the literature. In our case, a 59-year-old man with a history of widely metastatic prostate cancer presented to urgent care and was diagnosed with a nail plate avulsion injury. He was referred to hand surgery and treated with amputation of the right middle finger distal phalanx. The pathology reported high-grade poorly differentiated adenocarcinoma with primary lesion from the prostate.